2022
DOI: 10.3389/fgene.2022.927830
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization and Analysis of the bHLH Transcription Factor Family in Suaeda aralocaspica, an Annual Halophyte With Single-Cell C4 Anatomy

Abstract: Basic helix-loop-helix (bHLH) transcription factors play important roles in plant growth, development, metabolism, hormone signaling pathways, and responses to abiotic stresses. However, comprehensive genomic and functional analyses of bHLH genes have not yet been reported in desert euhalophytes. Suaeda aralocaspica, an annual C4 halophyte without Kranz anatomy, presents high photosynthetic efficiency in harsh natural habitats and is an ideal plant for identifying transcription factors involved in stress resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…A subset of genes, encompassing CtbHLH88, CtbHLH99, CtbHLH12, CtbHLH26, CtbHLH102, CtbHLH24, CtbHLH105, and CtbHLH6, are characterized by the presence of MBS elements (n = 1 each) (Figure S4). Compared to the findings in other plants [28,77], these bHLH members demonstrate an array of defense and stress-responsive elements, including the drought-inducible MBS element. In comparison to G-box and ABRE, MBS elements might hold a lesser significance than G-box elements.…”
Section: Discussionmentioning
confidence: 68%
“…A subset of genes, encompassing CtbHLH88, CtbHLH99, CtbHLH12, CtbHLH26, CtbHLH102, CtbHLH24, CtbHLH105, and CtbHLH6, are characterized by the presence of MBS elements (n = 1 each) (Figure S4). Compared to the findings in other plants [28,77], these bHLH members demonstrate an array of defense and stress-responsive elements, including the drought-inducible MBS element. In comparison to G-box and ABRE, MBS elements might hold a lesser significance than G-box elements.…”
Section: Discussionmentioning
confidence: 68%
“…Under drought stress, Arabidopsis AtMYC2 (bHLH) functions as a transcriptional activator in abscisic acid signaling and AtMYC2 and AtMYB2 proteins function as transcriptional activators in ABA-inducible gene expression in plants [42]. A number of cis-acting elements related to plant hormones and stress responses were also predicted in the promoter regions of SabHLHs, and most were involved in tolerance to drought and salinity [43]. In this study, the expression profile based on RNA-seq showed that most of the BpbHLH genes responded to osmotic treatment, indicating that these genes might be involved in drought resistance regulation mediated by the hormone signaling pathway in birch.…”
Section: Discussionmentioning
confidence: 99%
“… Phylogenetic analysis of the species based on genome-wide association study of the basic helix-loop-helix (bHLH) family. The total number of bHLH transcription factors identified from the genome of each species are indicated [ 5 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. …”
Section: Figurementioning
confidence: 99%